Adopsi Hukum Islam dalam Sistem Hukum Nasional (Kajian dalam UU RI No. 23 Tahun 2011 tentang Pengelolaan Zakat) - Muhammad Aziz (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2017)
Islamic law in Indonesia can be accepted into national law, because the formal judicial and normative, has become law lives in Indonesian society. However, when the Islamic law legislated into national law, many assume the principles of Islamic law or adopted reception is not great meinstrem in fiqh tradition, so create ripples resistance in applications in society, and even controversy. Based on this, the study would like to know the extent to which Islamic law on zakat adopted in Law No. 23 In 2011? Furthermore, this paper aims to reveal any of the Islamic law about this charity was adopted in Law No. 23 of 2011 concerning the management of zakat.This study concluded; that matter Law 23 of 2011 on the management of zakat which has become a national law was adopted from the main points of Islamic law in the field of management of zakat jurisprudence (fiqh al-zakâh), which includes several aspects: first, understanding aspects of zakat, infaq and Sadaqah; second, the distribution aspects of zakat (alms category); Third, the object aspect of zakat (mâl); The fourth aspect of the involvement of State/Government in the management of zakat (as âmilin); fifth, zakat management aspects of individual/private (non-government); and sixth, ‘âmil rights aspects.Keywords: Fiqh